An experimental study using manipulated photographs to examine interactions between micro-scale environmental factors for children's cycling for transport. (January 2018) - Ghekiere, Ariane; Deforche, Benedicte; De Bourdeaudhuij, Ilse; Clarys, Peter; Mertens, Lieze; Cardon, Greet; de Geus, Bas; Nasar, Jack; Van Cauwenberg, Jelle
Abstract: Installing cycling infrastructure well-separated from motorized traffic is hypothesized to increase children's transportation cycling. However, in some streets it may not be possible to install such cycling paths (e.g. due to financial or space constraints). The current paper investigates which physical factors could increase parents' perceptions of environmental supportiveness for children's transportation cycling, across six different types of cycling infrastructure. Parents completed a choice-based conjoint task by indicating which photographed street they preferred to let their child cycle along. The streets were experimentally manipulated on 7 physical factors (e.g. traffic speed, vegetation). Interactions between type of cycle path and the other environmental factors were identified. When no or limited separation from motorized traffic is present, street characteristics increasing parents' safety perceptions (traffic density and speed) should be prioritized when aiming to improve the supportiveness of streets for children's transportation cycling. Comfort and aesthetics can further improve streets' environmental supportiveness when cycling paths are more separated from traffic.